Analisis Makna di Balik Nama Warung Makan di Langsa Timur - Khairani, Naura; Sari, Nurmala; Nasywa, Dinda; Azzahrah, Afifah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to analyze the patterns, meanings, and factors that influence the naming of food stalls in the area. The method used is descriptive qualitative with an ethnolinguistic approach. Data were collected through direct observation, documentation, and interviews with food stall owners. The results show that the naming of food stalls in East Langsa is influenced by various aspects, such as the identity of the owner (personal or family name), the type of food sold, religious values, and elements of local and popular culture. Unique and contextualized naming is proven to provide a special attraction for consumers. This study contributes to the understanding of linguistic dynamics in the context of micro-enterprises and their relevance to the social and cultural identity of local communities.